Analysis Of Patient Service Quality At Kimia Farma Pettarani Clinic - Atira; A. Kartini Sari Putri D (International Journal of Management and Business Economics, 2023)
The analysis of the quality of patient service on Chemical Farma Cabang Clinic Pettarani. Thesis study Program Management Faculty of Economics and business of the University of Muhammadiyah Makassar. Guided by Tutors and Mentors Jusriadi Edi I II Muhammad Nur Abdi. The purpose of this research is "to know and analyze the quality of service to our satisfaction the patient on Clinic branch Farma Pettarani Chemistry". This research uses descriptive analysis with using this type of qualitative data, where data based on the data expressed in the form of a description of the information are obtained from the results of qualitative interviews. The results showed that patients feel satisfied in Clinical Chemistry against Farma Pettarani because of the speed and ketanggapan nurses as well as doctors in serving them Besides good greetings as well as manners also became a benchmark of patients to come back on the medication the clinic. Patient satisfaction factors to the quality of medical services will greatly affect the number of visits the patient into the clinic.